King Ralph [videorecording (DVD)] - Ward, David S., 1945-; O'Toole, Peter, 1932-2013; Richardson, Joely; Goodman, John, 1952-; Hurt, John, 1940-2017 (Vintage video., 2022)
A freak accident wipes out the British royal family, and sleazy American lounge singer Ralph suddenly finds himself the next King of England. However, it doesn₂t take long before Ralph realizes that it might not be so good to be the king after all.